Ionic-defect distribution revealed by improved evaluation of deep-level transient spectroscopy on perovskite solar sells - Reichert, Sebastian; Flemming, Jens; An, Qingzhi; Vaynzof, Yana (Physical review applied, 2020)
One of the key challenges for the future development of efficient and stable metal-halide perovskite solar cells is related to the migration of ions in these materials. Mobile ions have been linked to the observation of hysteresis in the current-voltage characteristics, shown to reduce device stability against degradation and act as recombination centers within the band gap of the active layer. In the literature, one finds a broad spread of reported ionic defect parameters (e.g., activation energies) for seemingly similar perovskite materials, rendering the identification of the nature of these species difficult. In this work, we perform temperature-dependent deep-level transient spectroscopy (DLTS) measurements on methylammonium-lead-iodide perovskite solar cells and develop a extended regularization algorithm for inverting the Laplace transform. Our results indicate that mobile ions form a distribution of emission rates (i.e., a distribution of diffusion constants) for each observed ionic species, which may be responsible for the differences in the previously reported defect parameters. Importantly, different DLTS modes such as optical and current DLTS yield the same defect distributions. Finally, the comparison of our results with conventional boxcar DLTS and impedance spectroscopy verifies our evaluation algorithm.
Gesehen am 08.04.2020